Heidi Heckelbeck is not a thief! - Coven, Wanda (Coven, Wanda. Heidi Heckelbeck, 2015)
Accused on stealing her best friend's cool new pen, young witch Heidi Heckelbeck must turn to her Book of Spells to clear her name.